Temporal Distribution and Nike Fishing Techniques at the Estuary of the Bone River - Sutrisno Sutrisno (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the pattern of temporal distribution and fishing techniques of Nike (Awaous sp.) In Gorontalo City. The research was conducted in October 2016 to January 2017 (Muharram to Jumadil - Early 1438 H). The method used is the method of random sampling and interviews. From the research results it is known that the temporal distribution pattern of Nike fish